Evolutionary rearrangements of X chromosomes in voles (Arvicolinae, Rodentia) - Romanenko, Svetlana A. (Sci Rep, 2020)
Euchromatic segments of the X chromosomes of placental mammals are the most conservative elements of the karyotype, only rarely subjected to either inter- or intrachromosomal rearrangements. Here, using microdissection-derived set of region-specific probes of Terricola savii we detailed the evolutionary rearrangements found in X chromosomes in 20 vole species (Arvicolinae, Rodentia). We show that the evolution of X chromosomes in this taxon was accompanied by multiple para- and pericentric inversions and centromere shifts. The contribution of intrachromosomal rearrangements to the karyotype evolution of Arvicolinae species was approximately equivalent in both the separate autosomal conserved segments and the X chromosomes. Intrachromosmal rearrangements and structural reorganization of the X chromosomes was likely accompanied by an accumulation, distribution, and evolution of repeated sequences.